-25=4u+3

Simple and best practice solution for -25=4u+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25=4u+3 equation:


Simplifying
-25 = 4u + 3

Reorder the terms:
-25 = 3 + 4u

Solving
-25 = 3 + 4u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-4u' to each side of the equation.
-25 + -4u = 3 + 4u + -4u

Combine like terms: 4u + -4u = 0
-25 + -4u = 3 + 0
-25 + -4u = 3

Add '25' to each side of the equation.
-25 + 25 + -4u = 3 + 25

Combine like terms: -25 + 25 = 0
0 + -4u = 3 + 25
-4u = 3 + 25

Combine like terms: 3 + 25 = 28
-4u = 28

Divide each side by '-4'.
u = -7

Simplifying
u = -7

See similar equations:

| 82-(4-6)2= | | 25n^8-49n^7-2n^6=0 | | -3+w=-4 | | -6=u-4 | | 5(2x-9)+3x=4x-18 | | 13=0.5((4x-10)+(3x+8)) | | 9x-(x+4)=2x+32 | | (1/7(x))+((1/7)x+1)+29=x | | 2x^1/2-7x^1/4+3=0 | | 63=.5h*9 | | 4x+7=54 | | 1/2*(3/5((2^3)-6))+1/5 | | 7/5x^2-7/9x-4/3x | | 1/2*3/5((2^3)-6)+1/5 | | 82x+4x=68.5 | | 5y+1/9=6y+5/9 | | 0.50x+0.05(80)=0.25(64) | | -8(x+5)+3=-37 | | 5x/14-3x/14-11x/14= | | -3x+2y+z=4 | | (3x+2)(5x-1)= | | (x-74)/x=0.4 | | m^4+4m^2+1=0 | | 0.08-0.01(x+2)=-0.02(3-x) | | 99=.5h+11 | | 6(y-1)/5=-2y | | 5x-2=5(x-4) | | 10x^2+3x+m=0 | | -3+6=x-10 | | x+x+x+3x=48 | | x^2+y^2=80 | | 3/7x+4/7=-8/7 |

Equations solver categories